Prospect of ultralight airplanes development - Adam KONICZEK; Robert KONIECZKA (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents characteristic of ultralight airplanes, rules and current interest of them. The purpose is to determine prospect of ultralight airplanes development on the basis of Civil Aviation Authority statistics analysis and trend of aviation market.